Factors Influencing Utilization of Ultrasound Scan Services among Pregnant Mothers at Ndejje Health Center IV, Wakiso District - Nakimera, Angella (Student's Journal of Health Research Africa, 2020)
Background: A study was carried out to identify the factors influencing the utilization of ultrasound scan services among pregnant mothers at Ndejje Health Centre IV, Wakiso District. Methodology: The study design was descriptive and cross-sectional and it employed both quantitative and qualitative data collection methods. A sample size of 30 respondents was selected using a simple random sampling procedure. An interview guide was used to collect data. Results: The study revealed various factors influencing the utilization of ultrasound scan services among pregnant mothers. For example, although all 30 (100%) had ever heard about ultrasound scan services, most 20 (66.7%) had ever used ultrasound scan services once 10 (50%) and 12 (60%) used the services in the 3rd trimester due to factors including 20 (66.7%) of ultrasound scan services, 21 (70%) having fears about using ultrasound scan services including 14 (66.7%) fear that the scan would identify bad conditions on the baby, 18 (60%) lacked partner support. The study results also revealed that respondents faced various health facility factors which influenced the utilization of ultrasound scan services. For example, most 20 (66.7%) respondents reported that Ndejje Health Centre IV was not equipped to provide ultrasound scan services due to 12 (60%) frequent breakdown and poor maintenance of equipment which led to 18 (60%) ultrasound scan services not being readily available, 12 (60%) long waiting time to receive services as most waited more than 2 hours to receive services. Conclusion and recommendations: Respondents faced various and health facility-related factors which influenced their utilization of ultrasound scan services. The key recommendations included ready availability of services through regular and timely maintenance of equipment, improving efficiency, and reducing waiting time as well as improved health education of mothers about the importance of using the services.